Protective Effect of Black Rice Cyanidin-3-Glucoside on Testicular Damage in STZ-Induced Type 1 Diabetic Rats - Hongxing Zheng; Yingjun Hu; Jia Zhou; Baolong Zhou; Shanshan Qi (Foods, 2024)
Diabetic testicular damage is quite a common and significant complication in diabetic men, which could result in infertility. The natural fertility rate of type 1 diabetes men is only 50% because of testicular damage. This research first aimed to explore the intervention effect of C3G on testicular tissue damage induced by diabetes. Here, a streptozotocin-induced type 1 diabetic rat model was established, and then C3G was administered. After 8 weeks of C3G supplementation, the symptoms of diabetes (e.g., high blood glucose, lower body weight, polydipsia, polyphagia) were relieved, and at the same time that sperm motility and viability increased, sperm abnormality decreased in C3G-treated diabetic rats. Furthermore, the pathological structure of testis was restored; the fibrosis of the testicular interstitial tissue was inhibited; and the LH, FSH, and testosterone levels were all increased in the C3G-treated groups. Testicular oxidative stress was relieved; serum and testicular inflammatory cytokines levels were significantly decreased in C3G-treated groups; levels of Bax, Caspase-3, TGF-β1 and Smad2/3 protein in testis decreased; and the level of Bcl-2 was up-regulated in the C3G-treated groups. A possible mechanism might be that C3G improved antioxidant capacity, relieved oxidative stress, increased anti-inflammatory cytokine expression, and inhibited the apoptosis of spermatogenic cells and testicular fibrosis, thus promoting the production of testosterone and repair of testicular function. In conclusion, this study is the first to reveal that testicular damage could be mitigated by C3G in type 1 diabetic rats. Our results provide a theoretical basis for the application of C3G in male reproductive injury caused by diabetes.